Virtual Interviews Correlate with Home and In-State Match Rates at One Emergency Medicine Program - Christine Motzkus; Casey Frey; Aloysius Humbert (Western Journal of Emergency Medicine)
Introduction: Incorporating virtual interviews into residency recruitment may help diversify access to residency programs while reducing the cost involved with travel and lodging. Programs may be more likely to rank students they have met in person at an interview when compared to unknown virtual applicants. Our objective was to characterize home institution, in-state, and in-region match rates to emergency medicine (EM) residency programs for fourth-year medical students. Methods: We used National Residency Matching Program data available to the program director to identify medical school and match location of fourth-year medical students who interviewed at a large EM residency program in the Midwest from 2018–2023. Students’ medical schools and ultimately matched programs were mapped to Electronic Residency Application Service geographic regions; subgroup analyses evaluated allopathic and osteopathic medical students separately. We used chi-square tests to compare proportions of students matching to home, in-state, or in-region programs across years. Results: There were 1,401 applicants with match information available. The percentage of students matching to a home institution remained stable over the course of the study. The percentage of students matching to an in-state institution increased over the first two years of virtual interviews rising from 23.2% in the 2020 match to 30.8% in-state matches for the 2022 match. Chi-square tests did not reveal any significant differences among groups for all applicants. Allopathic medical students demonstrated a significant increase in matches to home institutions. In-region matches stayed relatively stable over the study time frame regardless of subgroup. Conclusion: Virtual interviews changed the landscape of residency interviews. Home institution and in-state matches may be more likely for applicants from allopathic schools who participated in a virtual interview as both programs and applicants are more familiar with each other; however, our study did not find convincing evidence of this possibility among all applicants. Additional study is needed to determine ongoing effects of the transition to virtual interviews.